Welfare of the laying hen - Perry, G. C. [ (Graham C.)] (Wallingford, Oxfordshire : CABI Publishing, 2004)
The welfare of egg-producing poultry is a topic of great concern to the poultry industry and to researchers in applied animal behaviour. It is also subject to increased legislation. Issues such as battery cages, space requirements, access to daylight an ''free-range'' eggs have attracted public interest.
1. The stakeholders -- 2. Overviews -- 3. Welfare issues -- 4. Outcomes -- 5. Poster abstracts
Also available in electronic resource
Papers from the 27th Poultry Science Symposium held in Bristol, July 2003
Includes bibliographical references and index
Keywords: Hens -- Congresses; Poultry; Poultry -- Congresses